Application of anodic oxidation, electro-Fenton and UVA photoelectro-Fenton to decolorize and mineralize acidic solutions of Reactive Yellow 160 azo dye. (10th July 2016) - Bedolla-Guzman, Alejandro; Sirés, Ignasi; Thiam, Abdoulaye; Peralta-Hernández, Juan Manuel; Gutiérrez-Granados, Silvia; Brillas, Enric
Highlights: Slow decolorization of Reactive Yellow 160 solutions by anodic oxidation with a BDD/air-diffusion cell. Fast decolorization using electro-Fenton, even faster in UVA photoelectro-Fenton. 94-96% Mineralization by the most powerful UVA photoelectro-Fenton at 100 mA cm −2 . Maleic, fumaric, tartronic, acetic, oxalic, oxamic and formic acids detected as products. Cl −, SO4 2−, NH4 + and some NO3 − formed from heteroatoms during azo dye mineralization Abstract: The degradation of 100 cm 3 of a solution with 0.167 mmol dm −3 Reactive Yellow 160 (RY160) azo dye in sulfate medium at pH 3.0 has been comparatively studied by anodic oxidation with electrogenerated H2 O2 (AO-H2 O2 ), electro-Fenton (EF) and UVA photoelectro-Fenton (PEF). Trials were carried out with a stirred tank reactor equipped with a boron-doped diamond (BDD) anode and an air-diffusion cathode for H2 O2 production, upon addition of 0.50 mmol dm −3 Fe 2+ as catalyst in EF and PEF. The solution was slowly decolorized by AO-H2 O2 because of the low rate of reaction of the azo dye and its colored products with hydroxyl radicals generated at the BDD anode from water oxidation. The color loss was enhanced in EF by the larger oxidation ability of hydroxyl radicals produced in the bulk from Fenton's reaction between added Fe 2+ and generated H2 O2, whereas the solution was more rapidly decolorized by PEF owing to the additional generation of hydroxyl radicals from the photolysis of Fe(III)-hydroxy complexes by UVA light. The relative mineralization ability of the processes also increased in the sequence AO-H2 O2 < EF < PEF. The PEF method was the most powerful due to the synergistic oxidation by hydroxyl radicals and UVA irradiation, yielding 94% mineralization after 360 min at 100 mA cm −2 . The influence of current density and RY160 concentration on the performance of all processes was assessed. Final carboxylic acids like maleic, fumaric, tartronic, acetic, oxalic, oxamic and formic were quantified by ion-exclusion HPLC. All these acids were totally removed by PEF, but the formation of small amounts of other highly recalcitrant products impeded the total mineralization. Chloride, sulfate, ammonium and, to a smaller extent, nitrate ions were released to the solution from the heteroatoms of the azo dye in all cases.